De Mariano a Gurgel:: Um estudo de ocorrências intertextuais em uma homenagem a Cesar Camargo Mariano e Debora Gurgel (Orfeu, 2026)
This article addresses intertextuality as a central element in artistic creation, highlighting how musical works engage in dialogue with traditions and preexisting influences, reinterpreting and integrating them into new contexts. Drawing on Joseph Nathan Straus’s Theory of Musical Influence (1990) and the analytical nomenclature of Lucas Barbosa (2005), it explores how composers are shaped by their references and create through stylistic and idiomatic reinterpretations. Based on the analysis of De Mariano a Gurgel, composed by xxxxxx xxxxxx, the study identifies the use of musical elements characteristic of Cesar Camargo Mariano and Debora Gurgel, such as rhythmic, harmonic, and idiomatic motives drawn from their pianistic approaches. In this way, the text emphasizes intertextuality as a transformative process that bridges the old and the new, enriching artistic meaning and enabling multiple interpretations.